Synthesis and structure of heterometallic chromium(III) complexes with ethylenediaminetetraacetic acid [Articol] - Ciornea, Victor; Filippova, Irina; Gulea, Aurelian; Șova, Sergiu; Borta, A.; Simonov, Iurie (My University, 2005)
The complexes [M(Tsc)2][Cr(Edta)]2, where M is Ni, Cu; Tsc is thiosemicarbazide; Edta4- is the ethylenediaminetetraacetate anion, were synthesized and characterized by X-ray diffraction. The ionic structures are composed of the [M(Tsc)2] 2+ cations and [Cr(Edta)]- anions with a component ratio of 1 : 2. The cation has a distorted trans-square coordination. The carboxyl groups of the H4Edta molecule are deprotonated and the ligand is attached to the Cr atom in the hexadentate chelating mode. The cations and anions are linked by a system of hydrogen bonds.
Keywords: Engineering controlled terms Charge coupled devices; complexation; Hydrogen bonds; Negative ions; Superconducting materials; Synthesis (chemical); Thermal effects; X ray diffraction analysis Engineering uncontrolled terms Chromium complexes; Ethylenediaminetetraacetic acid (EDTA); Oxide materials; Water bath Engineering main heading Chromium